Preparation method of degradable biological magnesium alloy material for promoting bone healing

By preparing Mg-Li-Zn-Ag biomagnesium alloy material and uniformly distribute hydroxyapatite powder on the surface, the existing biomagnesium alloy material has limited effect in promoting bone healing and uneven distribution of the second phase, achieving complete degradation and biosafety of the material, significantly improving the bone healing effect and antibacterial properties.

CN119499441APending Publication Date: 2025-02-25JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411670874.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing biomagnesium alloy materials have limited effects in promoting bone healing, and the uneven distribution of the second phase has safety risks, which affects biosafety.

Method used

Mg-Li-Zn-Ag biomagnesium alloy material is prepared by smelting, homogenization, rolling, laser cladding and accumulation stacking, so as to ensure that the phase composition of the alloy is a complete solid solution structure and the hydroxyapatite powder is evenly distributed on the surface.

Benefits of technology

Complete degradation of biomagnesium alloy materials is achieved, the generation of the second phase is avoided, biosafety is ensured, and the release of Ag ions has antibacterial effects, significantly improving the mechanical properties and bone healing effect of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a degradable biological magnesium alloy material for promoting bone healing, and relates to the technical field of magnesium alloy materials.The preparation method comprises the following steps of smelting, homogenizing, rolling, laser cladding and accumulative ply rolling, the phase composition of the biological magnesium alloy is of a complete solid solution structure, and the biological magnesium alloy can be completely degraded in a living body; the biological magnesium alloy material has the advantages that the biological magnesium alloy material can be degraded, second-phase particles difficult to dissolve are not generated in the degradation process, the biological safety is guaranteed, the antibacterial effect can be achieved by adding a small amount of Ag element and releasing Ag ions in the in-vivo service process, the forming performance of the biological magnesium alloy material is guaranteed by adopting rolling and accumulative ply rolling, a foundation is laid for subsequent preparation of implantation devices, and the service life of the biological magnesium alloy material is prolonged. And the mechanical property of the alloy is remarkably improved through plastic deformation. By adopting the laser cladding, the fusion and re-solidification of the hydroxyapatite powder and the surface layer of the biological magnesium alloy are realized, the particles are not easy to aggregate in the subsequent accumulative ply rolling, and the uniform distribution of the hydroxyapatite powder in the subsequently prepared biological magnesium alloy material is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium alloy materials, and in particular to a method for preparing a degradable biological magnesium alloy material for promoting bone healing. Background Art

[0002] Magnesium alloys have a series of unique advantages in the field of bio-implantation: (1) Magnesium alloys have good biocompatibility. Mg is the largest metal element in the human body after Ca, Na and K. It can activate a variety of enzymes and participate in a series of metabolic processes in the body. Excessive Mg in the body can be excreted through urine, which has a good biosafety basis. In addition, Mg is an essential element for bone growth, which can promote the deposition of Ca and induce new bone formation; (2) Magnesium alloys have good mechanical compatibility. Magnesium alloys have high specific strength and specific stiffness, which can meet the mechanical performance requirements of bio-implant materials. Its elastic modulus is about 41-45GPa, which is much lower than that of stainless steel, titanium alloy and other materials, and is closer to the elastic modulus of human bone. It can effectively alleviate the stress shielding effect and promote bone growth and healing; (3) The standard electrode potential of pure Mg is only -2.37V. It is very easy to corrode in corrosive media. After completing the bone repair or fixation function, it can degrade in the human body, thereby avoiding secondary surgery and greatly reducing the risk and burden of patients.

[0003] However, the addition of alloying elements in existing bio-magnesium alloys leads to the generation of second phases. If these second phases are not decomposed in the human body for a long time, they will become a safety hazard. Secondly, bio-magnesium alloys mainly composed of alloy components have a limited effect on promoting bone healing. Bone healing after fracture takes a long time, which increases the patient's rehabilitation burden and the risk of secondary injury. The inorganic material hydroxyapatite is currently a commonly used magnesium alloy modification material to promote bone healing, but how to ensure the uniform distribution of hydroxyapatite in magnesium alloys has not been well solved. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a biodegradable magnesium alloy material that promotes bone healing, so as to overcome the above-mentioned defects in the prior art.

[0005] A method for preparing a biodegradable magnesium alloy material for promoting bone healing comprises the following steps:

[0006] S1. Melting: weighing Mg, Li, Zn and Ag as raw materials, placing the raw materials in a vacuum induction melting furnace, introducing argon gas as a protective atmosphere, and melting to obtain a Mg-Li-Zn-Ag bio-magnesium alloy ingot;

[0007] S2. Homogenization: placing the obtained bio-magnesium alloy ingot into a high-temperature atmosphere furnace, performing homogenization treatment under argon protection, and water quenching and cooling after homogenization;

[0008] S3, rolling: rolling the homogenized bio-magnesium alloy ingot into a sheet;

[0009] S4, laser cladding: using the prepared bio-magnesium alloy sheet as a substrate and hydroxyapatite powder as a cladding material, a layer of hydroxyapatite is clad on the surface of the substrate;

[0010] S5. Accumulative rolling: The prepared laser-clad bio-magnesium alloy plate is subjected to multiple passes of cumulative rolling, each pass is rolled to the original thickness of the plate, and between each pass, it is placed in a high-temperature atmosphere furnace for annealing treatment under argon atmosphere. After the last pass of cumulative rolling, no annealing treatment is performed, and a degradable bio-magnesium alloy material that promotes bone healing is obtained.

[0011] Preferably, the purity of the raw materials Mg, Li, Zn and Ag in step S1 is greater than or equal to 99.9wt%.

[0012] Preferably, the Mg-Li-Zn-Ag bio-magnesium alloy ingot obtained in step S1 has a Li content of 2-3 wt.%, a Zn content of 1-2 wt.%, and an Ag content of 0.2-0.4 wt.%.

[0013] Preferably, in step S2, the homogenization temperature is 450-500° C., and the homogenization time is 8-16 hours.

[0014] Preferably, the rolling temperature in step S3 is 200-300° C., and the thickness of the sheet after rolling is 1-2 mm.

[0015] Preferably, during the laser cladding process in step S4, the laser power is 300-500 W, the scanning speed is 800-1200 mm / min, the powder thickness of the cladding layer is 30-60 μm, and the powder is spread in a single layer.

[0016] Preferably, in step S5, the cumulative rolling temperature is 200-300° C., the cumulative rolling layers are 3-5 layers, the top plate is made of bio-magnesium alloy sheet that has not been laser clad, and the cumulative rolling is performed for 4-6 times.

[0017] Preferably, in step S5, the annealing temperature is 150-250° C., and the annealing time is 5-15 min.

[0018] The beneficial effects achieved by the present invention are:

[0019] ① The bio-magnesium alloy used in the present invention has a phase composition of a complete solid solution structure prepared by reasonably selecting alloy elements and controlling the content. It can be completely degraded in the body and no insoluble second phase particles are produced during the degradation process, thereby ensuring biological safety.

[0020] ② The biological magnesium alloy used in the present invention releases Ag ions during service in the body by adding a small amount of Ag element, which can play an antibacterial role.

[0021] ③ The present invention adopts rolling and cumulative lamination, which not only ensures the forming performance of the biological magnesium alloy material, laying a foundation for the subsequent preparation of implant devices, but also significantly improves the mechanical properties of the alloy through plastic deformation.

[0022] ④ The present invention uses laser cladding to achieve the melting and resolidification of hydroxyapatite powder and the surface layer of the biological magnesium alloy. In the subsequent cumulative rolling, the particles are not easy to aggregate, thereby ensuring the uniform distribution of hydroxyapatite powder in the subsequent biological magnesium alloy material. DETAILED DESCRIPTION

[0023] The specific implementation modes of the present invention are further explained in detail below through the description of embodiments, so as to help those skilled in the art to have a more complete, accurate and in-depth understanding of the concept and technical solution of the present invention.

[0024] Example 1

[0025] A method for preparing a biodegradable magnesium alloy material for promoting bone healing comprises the following steps:

[0026] S1. Melting: According to the target composition, weigh 99.9wt% pure metal Mg, Li, Zn and Ag as raw materials, place the raw materials in a vacuum induction melting furnace, introduce argon as a protective atmosphere, and melt to obtain a Mg-Li-Zn-Ag bio-magnesium alloy ingot, wherein the Li content is 2wt.%, the Zn content is 1wt.%, and the Ag content is 0.2wt.%;

[0027] S2. Homogenization: placing the obtained bio-magnesium alloy ingot into a high-temperature atmosphere furnace and performing homogenization treatment under argon protection at a homogenization temperature of 450°C for 16 hours. After homogenization, water quenching is performed;

[0028] S3, rolling: rolling the homogenized bio-magnesium alloy ingot into a sheet material, the rolling temperature is 200° C., and the thickness of the sheet material after rolling is 1 mm;

[0029] S4, laser cladding: using the prepared bio-magnesium alloy sheet as the substrate and hydroxyapatite powder as the cladding material, a layer of hydroxyapatite is clad on the surface of the substrate. During the laser cladding process, the laser power is 300W, the scanning speed is 800mm / min, the cladding layer powder thickness is 30μm, and the powder is spread in a single layer;

[0030] S5. Cumulative rolling: The prepared laser-clad bio-magnesium alloy plate is subjected to cumulative rolling, the cumulative rolling temperature is 200°C, the cumulative rolling layers are 5, the top plate is made of bio-magnesium alloy plate that has not been laser-clad, and the cumulative rolling is performed for 6 times, each time the plate is rolled to its original thickness, and between each time the plate is placed in a high-temperature atmosphere furnace for annealing in an argon atmosphere, the annealing temperature is 250°C, the annealing time is 5 minutes, and no annealing is performed after the last cumulative rolling, thereby obtaining a degradable bio-magnesium alloy material that promotes bone healing.

[0031] According to GB / T228-2010 "Tensile Test of Metal Materials", the tensile strength of the bio-magnesium alloy was measured to be 321MPa. According to ASTMG31-1972 (2004) "Standard Practice for Lab Immersion Corrosion Testing of Metals", the corrosion performance test was carried out, the corrosive medium was simulated body fluid, the temperature was maintained at 36.5±0.5℃, and the simulated body fluid was replaced every 24 hours. The test results showed that the corrosion rate of the bio-magnesium alloy was 0.12mm / year.

[0032] Example 2

[0033] A method for preparing a biodegradable magnesium alloy material for promoting bone healing comprises the following steps:

[0034] S1. Melting: According to the target composition, weigh 99.9wt% pure metal Mg, Li, Zn and Ag as raw materials, place the raw materials in a vacuum induction melting furnace, introduce argon as a protective atmosphere, and melt to obtain a Mg-Li-Zn-Ag bio-magnesium alloy ingot, wherein the Li content is 3wt.%, the Zn content is 2wt.%, and the Ag content is 0.4wt.%;

[0035] S2: Homogenization: The obtained bio-magnesium alloy ingot is placed in a high-temperature atmosphere furnace and homogenized under argon protection. The homogenization temperature is 500°C and the homogenization time is 8 hours. After the homogenization is completed, the ingot is water quenched and cooled;

[0036] S3, rolling: rolling the homogenized bio-magnesium alloy ingot into a sheet material, the rolling temperature is 300° C., and the thickness of the sheet material after rolling is 2 mm;

[0037] S4, laser cladding: using the prepared bio-magnesium alloy sheet as the substrate and hydroxyapatite powder as the cladding material, a layer of hydroxyapatite is clad on the surface of the substrate. During the laser cladding process, the laser power is 500W, the scanning speed is 1200mm / min, the cladding layer powder thickness is 60μm, and the powder is spread in a single layer;

[0038] S5. Cumulative rolling: The prepared laser-clad bio-magnesium alloy sheet is subjected to cumulative rolling, the cumulative rolling temperature is 300°C, the cumulative rolling layers are 3, the top layer of the sheet is the bio-magnesium alloy sheet that has not been laser-clad, the cumulative rolling is performed for 4 passes, each pass is rolled to the original thickness of the sheet, and between each pass, it is placed in a high-temperature atmosphere furnace for annealing in an argon atmosphere, the annealing temperature is 150°C, the annealing time is 15 minutes, and no annealing is performed after the last pass of cumulative rolling, so as to obtain a degradable bio-magnesium alloy material that promotes bone healing.

[0039] According to GB / T228-2010 "Metallic Material Tensile Test", the tensile strength of the bio-magnesium alloy was measured to be 298MPa. According to ASTMG31-1972 (2004) "Standard Practice for Lab Immersion Corrosion Testing of Metals", the corrosion performance test was carried out, the corrosive medium was simulated body fluid, the temperature was maintained at 36.5±0.5℃, and the simulated body fluid was replaced every 24 hours. The test results showed that the corrosion rate of the bio-magnesium alloy was 0.15mm / year.

[0040] Example 3

[0041] A method for preparing a biodegradable magnesium alloy material for promoting bone healing comprises the following steps:

[0042] S1. Melting: According to the target composition, weigh 99.9wt% pure metal Mg, Li, Zn and Ag as raw materials, place the raw materials in a vacuum induction melting furnace, introduce argon as a protective atmosphere, and melt to obtain Mg-Li-Zn-Ag bio-magnesium alloy ingots, wherein the Li content is 2.5wt.%, the Zn content is 1.5wt.%, and the Ag content is 0.3wt.%;

[0043] S2, homogenization: placing the bio-magnesium alloy ingot obtained in step 1 into a high-temperature atmosphere furnace, and performing homogenization treatment under argon protection, the homogenization temperature is 475°C, the homogenization time is 12h, and after the homogenization is completed, water quenching is performed;

[0044] S3, rolling: rolling the homogenized bio-magnesium alloy ingot obtained in step 2 into a sheet material, the rolling temperature is 250° C., and the thickness of the sheet material after rolling is 1.5 mm;

[0045] S4, laser cladding: using the bio-magnesium alloy sheet prepared in step 3 as the substrate, and hydroxyapatite powder as the cladding material, a layer of hydroxyapatite is clad on the surface of the substrate. During the laser cladding process, the laser power is 400 W, the scanning speed is 1000 mm / min, the cladding layer powder thickness is 45 μm, and the powder is spread in a single layer;

[0046] S5. Cumulative rolling: the laser-clad bio-magnesium alloy sheet obtained in step 4 is subjected to cumulative rolling, the cumulative rolling temperature is 250°C, the cumulative rolling layers are 4, the top layer of the sheet is the bio-magnesium alloy sheet that has not been laser-clad, the cumulative rolling is performed for 5 passes, each pass is rolled to the original thickness of the sheet, and between each pass, the sheet is placed in a high-temperature atmosphere furnace for annealing in an argon atmosphere, the annealing temperature is 200°C, the annealing time is 10 minutes, and no annealing is performed after the last pass of cumulative rolling, so as to obtain a degradable bio-magnesium alloy material that promotes bone healing.

[0047] According to GB / T228-2010 "Tensile Test of Metal Materials", the tensile strength of the bio-magnesium alloy was measured to be 305MPa. According to ASTMG31-1972 (2004) "Standard Practice for Lab Immersion Corrosion Testing of Metals", the corrosion performance test was carried out, the corrosive medium was simulated body fluid, the temperature was maintained at 36.5±0.5℃, and the simulated body fluid was replaced every 24 hours. The test results showed that the corrosion rate of the bio-magnesium alloy was 0.13mm / year.

[0048] The above-described embodiments of the present invention do not constitute a limitation on the protection scope of the present invention. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a biodegradable magnesium alloy material for promoting bone healing, characterized in that: The following steps are involved: S1. Melting: weighing Mg, Li, Zn and Ag as raw materials, placing the raw materials in a vacuum induction melting furnace, introducing argon gas as a protective atmosphere, and melting to obtain a Mg-Li-Zn-Ag bio-magnesium alloy ingot; S2. Homogenization: placing the obtained bio-magnesium alloy ingot into a high-temperature atmosphere furnace, performing homogenization treatment under argon protection, and water quenching and cooling after homogenization; S3, rolling: rolling the homogenized bio-magnesium alloy ingot into a sheet; S4, laser cladding: using the prepared bio-magnesium alloy sheet as a substrate and hydroxyapatite powder as a cladding material, a layer of hydroxyapatite is clad on the surface of the substrate; S5. Accumulative rolling: The prepared laser-clad bio-magnesium alloy plate is subjected to multiple passes of cumulative rolling, each pass is rolled to the original thickness of the plate, and between each pass, it is placed in a high-temperature atmosphere furnace for annealing treatment under argon atmosphere. After the last pass of cumulative rolling, no annealing treatment is performed, and a degradable bio-magnesium alloy material that promotes bone healing is obtained.

2. The method for preparing a biodegradable magnesium alloy material for promoting bone healing according to claim 1, characterized in that: In step S1, the purity of the raw materials Mg, Li, Zn and Ag is greater than or equal to 99.9wt%.

3. The method for preparing a biodegradable magnesium alloy material for promoting bone healing according to claim 1, characterized in that: The Mg-Li-Zn-Ag bio-magnesium alloy ingot obtained in step S1 has a Li content of 2-3 wt.%, a Zn content of 1-2 wt.%, and an Ag content of 0.2-0.4 wt.%.

4. The method for preparing a biodegradable magnesium alloy material for promoting bone healing according to claim 1, characterized in that: In step S2, the homogenization temperature is 450-500° C., and the homogenization time is 8-16 hours.

5. The method for preparing a biodegradable magnesium alloy material for promoting bone healing according to claim 1, characterized in that: In step S3, the rolling temperature is 200-300° C., and the thickness of the sheet after rolling is 1-2 mm.

6. The method for preparing a biodegradable magnesium alloy material for promoting bone healing according to claim 1, characterized in that: During the laser cladding process in step S4, the laser power is 300-500 W, the scanning speed is 800-1200 mm / min, the powder thickness of the cladding layer is 30-60 μm, and the powder is spread in a single layer.

7. The method for preparing a biodegradable magnesium alloy material for promoting bone healing according to claim 1, characterized in that: In step S5, the cumulative rolling temperature is 200-300° C., the cumulative rolling layers are 3-5 layers, the top plate is made of bio-magnesium alloy plate that has not been laser clad, and the cumulative rolling is performed for 4-6 times.

8. The method for preparing a biodegradable magnesium alloy material for promoting bone healing according to claim 1, characterized in that: In step S5, the annealing temperature is 150-250° C., and the annealing time is 5-15 minutes.